2015
DOI: 10.1063/1.4918703
|View full text |Cite
|
Sign up to set email alerts
|

Effective phonon mean free path in polycrystalline nanostructures

Abstract: We have calculated the mean free path (MFP) of phonons associated with grain boundary scattering in polycrystalline nanostructures, by developing a Monte Carlo ray tracing transmission model that can be applied to arbitrary geometries. The calculations for various log-normal grain-size distributions realized by Voronoi diagrams and genetic algorithms show that the boundary-scattering MFP in a polycrystalline nanostructure is 20%–30% longer than that in a simple cubic structure with the same average grain size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 38 publications
1
59
0
Order By: Relevance
“…We obtain the long length limit Λ B from the slope of L / Λ against L , which isolates the intrinsic diffusive boundary scattering from the ballistic end effects4748. We have validated the ray tracing code against analytical solutions for Λ B , including nanowires44 and cross-plane transport in diffuse superlattices49, as well as previously published BTE simulation results for two nanomeshes21 (see Supplementary Note 4 and Supplementary Fig. 4).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…We obtain the long length limit Λ B from the slope of L / Λ against L , which isolates the intrinsic diffusive boundary scattering from the ballistic end effects4748. We have validated the ray tracing code against analytical solutions for Λ B , including nanowires44 and cross-plane transport in diffuse superlattices49, as well as previously published BTE simulation results for two nanomeshes21 (see Supplementary Note 4 and Supplementary Fig. 4).…”
Section: Resultsmentioning
confidence: 77%
“…Analytical results for are known for simple geometries such as nanowires4243, but Λ B is generally unknown for complicated structures such as the nanomesh1520. To rigorously determine Λ B we use a ray tracing technique44. From the Landauer-Büttiker formalism4546, the thermal conductance G is…”
Section: Resultsmentioning
confidence: 99%
“…However, the maximum thermal conductivity in the sample with average grain size of 0.55 μm, 5.2 Wm -1 K -1 , is much lower than that in 190 nm-thick film, 23 Wm -1 K -1 [23], which indicates suitability of nanostructuring for reducing thermal conductivity. Note that the previous phonon transport calculations of silicon nanocrystalline structures have shown that the grain-size dependence of thermal conductivity is insensitive to the width of size distribution and determined by the average size [24].…”
Section: Resultsmentioning
confidence: 99%
“…At grain/phase boundaries that are comparable to grain size, a significant amount of heat is transported through the interface by phonons [56], therefore studying the high pressure 2H phase of CuAlO2 can help elucidate phonon transport in nano--grained structures of the 3R phase as well. The grain boundary scattering term is the only term that depends on the direction of the phonon group velocity explicitly, which can generally be expressed as the frequency independent equation [57],…”
Section: B Grain Boundariesmentioning
confidence: 99%